SAP on AWS in Education: Transforming Digital Learning Environments - Shamshuddin Shaik, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating SAP Enterprise Resource Planning (ERP) systems with Amazon Web Services (AWS) is transforming educational institutions to change the face of operational competency and ways of knowledge delivery. It will discuss the cloud-based infrastructure and how it benefits educational organizations in terms of scalability, cost optimization, and robust disaster recovery strategies. This article will assess how SAP on AWS implements automation processes in administrative work, data-driven decision-making, and personalized learning experiences. The article addresses critical security and compliance considerations indispensable for protecting sensitive educational data while maintaining regulatory adherence. It addresses best practices around implementation, from architecture planning down to performance-optimization strategy and change-management approach. To top it off, the article analyses the future scope of educational technology, which is very much concerned with the emerging themes of artificial intelligence, the Internet of Things, blockchain, and extended reality, leading to a redrawing of educational landscapes. The article provides insight into how educational institutions can use these technological advancements to enhance operational efficiency while maintaining security and compliance in an increasingly digital educational environment.
Keywords: Educational Cloud Computing; SAP Implementation; Digital Learning Transformation; Educational Data Security; Educational Technology Integration